Existence of Periodic Solutions of Linear Hamiltonian Systems with Sublinear Perturbation. (6th April 2010) - Han, Zhiqing
Abstract : We investigate the existence of periodic solutions of linear Hamiltonian systems with a nonlinear perturbation. Under generalized Ahmad-Lazer-Paul type coercive conditions for the nonlinearity on the kernel of the linear part, existence of periodic solutions is obtained by saddle point theorems. A note on a result of Rabinowitz is also given.